An experimental analysis on the transverse crushing behaviour of Nano-filler reinforced composite cylindrical tubular elements. Issue 1 (February 2021) - Kumar, Praveen; Shunmugasundaram, M.; Sivasankar, S.; Baig, Maughal Ahmed Ali; PonrajSankar, L.
Abstract: Thin-walled structures made of nanocomposite materials, could be employed as energy dissipating tubular elements in automobiles owing to its significant characteristics such as lightweight, fracture toughness, enhanced stiffness, and impact energy absorbing ability. The current research work aimed to investigate the transverse deformation behaviour of the hybrid aluminium-nano-filler reinforced glass/basalt fabric polymer composite cylindrical tubes under quasi-static experiments. The progressive crushing behaviour of these tubes were examined from photography. The experimental outcomes revealed that the aluminium-nano-filler reinforced composite tubes buckled displaying an ability of spreading the deformation under transverse compression. The use of multi-walled carbon nano tube fillers reduced the fibre fracturing and ultimately improved the energy absorbing ability of the tubes during crushing process. The nano filler induced tubes with more fabric plies revealed marginally better crashworthiness performance compared to the traditional aluminium-glass/basalt fabric polymer composite tubes.